Control and Central Monitoring of a Large Multipurpose Water Delivery System - Rijo, Manuel (2001)
This paper presents the first approach to the centralized SCADA system and automation of the Multipurpose Alqueva Project (MAP). MAP is located in the South of Portugal, mainly in the Guadiana River Basin. It will transfer water to the Sado River Basin. The MAP water delivery control system will guarantee on-line water demands and minimizes water operational losses and energy costs due to pumping. A general modular and hierarchical configuration for the control system is presented. Each component is described and automatic/manual control loops at higher levels are discussed. In the MAP central monitoring, one of the main issue is the communication system that links the remote sites to the central room. According to the specific characteristics, an economic and technical analysis is conducted for several possible architectures. The necessary equipment at the remote sister to link them to the central room is described. The architecture for the central monitoring room is also presented.